PENERAPAN PRINSIP KEHATI-HATIAN BANK DALAM PENCAIRAN DANA NASABAH DIHUBUNGKAN DENGAN UNDANG-UNDANG TENTANG PERBANKAN - Eka Sukarini, Eri; Juliastuti, Shofi (Yustitia, 2021)
Banks, especially commercial banks, are not only financial intermediaries from those with surplus funds to those with deficit funds, but are also the financial foundation of every country engaged in business activities and the various services provided. Banks serve and launch payment system mechanisms for all sectors of the economy. As a financial institution, bank activities are based on the trust of customers who can be accounted for by the bank. The Bank as an Intermediary institution carries out its business activities based on banking principles and rules, one of which is the Prudential Principle which must be applied. Themethodology used in this research is a normative juridical approach, namely by collecting library data by examining library materials or secondary legal materials. In this case, by examining the legal issues contained in Court Decision Number 38/Pdt.G/2017/PN.Idm and Act Number 10, 1998. The precautionary principle as a form of legal protection forcustomers indirectly to anticipate losses to customers. Which should be implemented properly to maintain customer trust, but in its implementation the precautionary principle has not been applied optimally. This has been encountered in one of the cases where the bank was deemed not to have maximally implemented the prudential principles. Proof (validation) of the system, the Bank should apply the precautionary principle but in its implementation the Bank causes losses to customers and the loss of customer trust in the Bank.